Aesop's fables aesop - Zipes, Jack (London, Penguin books Ltd, 1996)
Timeless tales of inspiration and enlightenment In ancient Greece, a storyteller named Aesop captivated his listeners with tales both beautiful and instructive. Thousands of years later, his fables--from The Ant and the Grasshopper to The Boy Who Cried Wolf to The Goose That Laid the Golden Egg to The Tortoise and the Hare--have lost none of their power to guide and entertain.
Keywords: English fiction